Correlation Between Company Condition and Work Achievement Of Employees in PT. Plantation Nusantara IV Balimbingan Plantation - Authar ND, Muhammad; Puteh, Anwar; Pane, Amelia; Alfiady, Teuku (International Journal of Engineering, Science and Information Technology, 2021)
The role of human resource management is reflected in the company's policy to regulate its human resources so that it can play a major role in working together and supporting the company's strategy by measuring the level of employee performance. Employee work performance is strongly influenced by the condition of company such as motivation factors, job satisfaction, working stress, physical condition of work, compensation system, and job design. The purpose of this study was to determine the relationship of motivation factors, job satisfaction, working stress, physical condition of work, compensation system, and job design with employee performance at PT. Perkebunan Nusantara IV Unit Kebun Balimbingan. This research was carried out at PT. Perkebunan Nusantara IV Unit Kebun Balimbingan in May 2018. This study uses non-parametric analysis with Kendall Tau test. The results showed that the factors of motivation, job satisfaction, work stress, physical condition of work, compensation system and job design were partially related to employee performance because of the significance value (0.000 0.05). Motivation factors, job satisfaction, physical condition of work and compensation system are strongly related and the direction of a positive relationship with work performance is the correlation coefficient values of 0.895, 0.720, 0.733 and 0.706, respectively. Job stress factors are negatively related to work performance with a correlation coefficient value of -0.550. Job design factors are positively related to a low correlation level of 0.377. Simultaneously the six factors are significantly related to work performance because the value of Asymp.Sig 0.05